The Use of Microsoft Sway 365 in Teaching Reading Descriptive Text: A Response to Pandemic Situation - Rini Khairunnisa Usman; Akhmad Baihaqi (Journal of English Language Teaching and Cultural Studies, 2020)
The aim of the study is to investigate the use of Microsoft Sway 365 in teaching reading descriptive text as a response in pandemic situation. The method used in the research was classroom action research. Subject of the research was 36 students from tenth grade of SMAN 1 Baros, Banten Province. Data collective techniques used in this recent study were test and questionnaire. The result of research shows that students achieve average scores 67.5 from reading test in pre-cycle. This result, of course, still lower than the ideal score 75. Since Sway Microsoft 365 is implemented, students’ scores are increased. This can be seen from the average score in cycle 1 is 77.5; and it increases into 81.5 in cycle 2. These results also matched to the questionnaire result which 78% of students agree if Microsoft Sway 365 can be used as an alternative online learning media for reading descriptive text, especially proposed for pandemic situation.